2017
DOI: 10.1111/febs.14165
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical investigation of type A PutAs reveals a conserved core oligomeric structure

Abstract: Many enzymes form homooligomers, yet the functional significance of self-association is seldom obvious. Herein, we examine the connection between oligomerization and catalytic function for proline utilization A (PutA) enzymes. PutAs are bifunctional enzymes that catalyze both reactions of proline catabolism. Type A PutAs are the smallest members of the family, possessing a minimal domain architecture consisting of N-terminal proline dehydrogenase and C-terminal L-glutamate-γ-semialdehyde dehydrogenase modules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 77 publications
6
37
0
Order By: Relevance
“…Thus, initial fitting to the experimental curves was carried out using only the tetramer model. The χ values obtained from fits to the crystallographic tetramer alone were in the range of 4.1–8.5, and there was a noticeable mismatch between the theoretical and experimental curves in both the Guinier region and the valley near q of 0.05–0.075 . This result indicated that the tetramer alone may not be sufficient to explain the experimental data.…”
Section: Determination Of Protein Quaternary Structure From Saxsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, initial fitting to the experimental curves was carried out using only the tetramer model. The χ values obtained from fits to the crystallographic tetramer alone were in the range of 4.1–8.5, and there was a noticeable mismatch between the theoretical and experimental curves in both the Guinier region and the valley near q of 0.05–0.075 . This result indicated that the tetramer alone may not be sufficient to explain the experimental data.…”
Section: Determination Of Protein Quaternary Structure From Saxsmentioning
confidence: 93%
“…The v values obtained from fits to the crystallographic tetramer alone were in the range of 4.1-8.5, and there was a noticeable mismatch between the theoretical and experimental curves in both the Guinier region and the valley near q of 0.05-0.075. 53 This result indicated that the tetramer alone may not be sufficient to explain the experimental data. To address this issue, MultiFoXS fitting was employed using all three models (dimer 1, dimer 2, and tetramer).…”
Section: Case 4: a Subtle Dimer-tetramer Equilibriummentioning
confidence: 95%
“…The GsPutA catalog includes complexes of the oxidized enzyme with proline analogs, structures of the enzyme in the 2-electron FAD reduced state, and a structure with the model electron acceptor menadione bisulfite (MB) bound in the PRODH active site. Also, the structure of another class 2A PutA was reported recently (PutA from Bdellovibrio bacteriovorus , BbPutA) [33]. …”
Section: Three-dimensional Structure Of Putamentioning
confidence: 99%
“…No other PutA studied to date forms this tetramer, so its functional significance is a matter of speculation. Recently, Korasick and coworkers showed that engineered dimeric forms of BjPutA retain full catalytic activity, suggesting that tetramerization is not essential for in vitro activity [33]. Whether the tetramer is needed for in vivo function remains to be studied.…”
Section: Three-dimensional Structure Of Putamentioning
confidence: 99%
“…PutAs in the type A class contain the two catalytic domains and are the best structurally characterized with high-resolution crystal structures of PutA from Bradyrhizobium japonicum ( Bj PutA), 27 Geobacter sulfurreducens ( Gs PutA), 28 and Bdellovibrio bacteriovorus . 34 Type B PutAs are distinguished by an additional C-terminal domain that was recently identified as an aldehyde dehydrogenase superfamily (ALDHSF) fold. Characterization of type B PutAs from Sinorhizobium meliloti 29 and Corynebacteirum freiburgense 35 showed that the major function of the C-terminal ALDHSF domain is to stabilize aldehyde binding in the GSALDH active site and seal the substrate channel from bulk solvent.…”
mentioning
confidence: 99%